2019
DOI: 10.1016/j.bbi.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Family-based analyses reveal novel genetic overlap between cytokine interleukin-8 and risk for suicide attempt

Abstract: Background-Suicide is major public health concern. It is imperative to find robust biomarkers so that at-risk individuals can be identified in a timely and reliable manner. Previous work suggests mechanistic links between increased cytokines and risk for suicide, but questions remain regarding the etiology of this association, as well as the roles of sex and BMI. Methods-Analyses were conducted using a randomly-ascertained extended-pedigree sample of 1882 Mexican-American individuals (60% female, mean age=42.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 100 publications
1
4
0
Order By: Relevance
“…One previous study showed that the plasma IL-8/IL-10 ratio together with salivary cortisol predicted EPDS scores indicative of depression in the post-partum (Corwin et al, 2015), which is in line with our data. Interestingly, both IL-8 levels and genotypes have been linked to suicidality in clinical cohorts (Janelidze et al, 2015;Isung et al, 2012, Noorozi et al, 2018, Knowles et al, 2019. At the same time, we found here that decreased levels of IL-2 also increased the risk for peripartum depression, which to the best of our knowledge has not been reported previously.…”
Section: Discussionsupporting
confidence: 75%
“…One previous study showed that the plasma IL-8/IL-10 ratio together with salivary cortisol predicted EPDS scores indicative of depression in the post-partum (Corwin et al, 2015), which is in line with our data. Interestingly, both IL-8 levels and genotypes have been linked to suicidality in clinical cohorts (Janelidze et al, 2015;Isung et al, 2012, Noorozi et al, 2018, Knowles et al, 2019. At the same time, we found here that decreased levels of IL-2 also increased the risk for peripartum depression, which to the best of our knowledge has not been reported previously.…”
Section: Discussionsupporting
confidence: 75%
“…Four studies analyzed the existence of inflammatory cytokines abnormalities in suicidal patients (having both a positive history of suicide attempts and suicidal ideation) and eventually healthy controls. First, Knowles et al [33] tried to identify a possible link between increased inflammatory cytokines and suicide risk and reported that IL-8 and IL-6 shared a significant genetic overlap with risk of suicide attempts (for IL-6 this risk was attenuated when body mass index (BMI) was included as a covariate). Relevantly, the genetic overlap between IL-8 and risk for suicide attempts was significant in females but not males.…”
Section: Studies Analyzing Inflammatory Abnormalities In Suicidal Patmentioning
confidence: 99%
“…However, based on the selected studies and in line with a previously published paper of our research group upon the same topic [7], the existence of an association between inflammatory cytokines abnormalities and suicidal behavior does not necessarily reflect a specific causal link. Among the selected studies, eleven reports [8,9,12,[25][26][27][28][29][30][31][32] analyzed inflammatory cytokines abnormalities in suicidal patients, four [33][34][35][36] explored cytokines abnormalities in patients with both a positive history of suicide attempts and suicidal ideation, two [37,38] investigated the existence of inflammatory cytokines abnormalities levels in depressed patients with suicidal ideation vs. those abnormally without, seven [31,[40][41][42][43][44]50] examined the inflammatory cytokines abnormalities in patients with a history of suicide attempts vs. those without, three [45][46][47] analyzed patients died by suicide vs. those died for other causes, and two [48,49] focused on depressed suicidal patients with suicidality.…”
Section: Summary Of Main Findings and Review Of Study Designsmentioning
confidence: 99%
“…In a previous GWAS, strongest candidate genes of suicidal behaviour were linked to inflammatory response (42), and recent studies identifying top ranking molecular markers predicting suicidal ideation lead to 8 genes including IL6 (besides SAT1, SKA2, SLC4A4, KIF2C, MBP, JUN, and KLHDC3) (16,43,44). The imbalance between anti-and proinflammatory cytokines in suicidal behaviour also suggests that cytokine genes may be putative contributors of suicide risk (45), with heritability for IL-6 levels estimated in twin studies ranging between 0.25 and 0.26 when taking into account confounding factors such as BMI (46).…”
Section: The Effect Of Il6 Gene On Suicidal Behaviourmentioning
confidence: 99%